Experimental and CFD analyses of a thermal radiation shield dimple plate for cryogenic pump application. Issue 1 (November 2015) - Scannapiego, M; Day, C
Abstract: Large customized cryogenic pumps are used in fusion reactors to evacuate the plasma exhaust from the torus. Cryopumps usually consist of an active pumping surface area cooled below 5 K and shielded from direct outer thermal radiation by plates cooled at 80K. In nuclear fusion applications, cryopumps are exposed to excessively high heat fluxes during pumping operation, and follow-up regeneration cycles with rapid warm-up and cool-down phases. Therefore, high cryogenic operational mass flows are required and thus pressure drop and heat transfer characteristics become key issues for the design of the pump cryogenic circuits. Actively cooled dimple plates are a preferred design solution for the thermal radiation shield. A test plate with a rhomb pattern of dimples has been manufactured and tested in terms of pressure drop with a dedicated test facility using water. In the present work, computational fluid dynamics (CFD) models of the test dimple plate have been performed, and computed pressure drops have been compared to experimental results. Despite the complexity of the geometry, a good agreement with the experimental results was found. Then, the validated CFD approach has been further extended to relevant operation conditions, using gaseous helium at cryogenic temperature as working fluid. The resulting pressure drop and heat transfer characteristics are finally presented.